The Role of R&D Intensity on the Export Intensity of Enterprises in Transition Economy: The Case of Vietnam - Tu Van, Binh; Vo Van, Dut; Lan Ngoc Trang, Thanh (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research paper Research aims: This study estimates the role of research and development (R&D) expense with respect to the export intensity of Vietnamese enterprises. Design/Methodology/Approach: Building upon the resource-based review, this study postulates that the R&D expenses of an enterprise are positively associated with the export intensity of the enterprise. Data extracted from the Vietnam General Statistics Office Survey of 306 exporting Vietnamese firms were used to test the proposed hypothesis. Research Findings: Both Robust Standard Errors and Tobit Regression models reveal that the hypothesis is strongly supported with the control of firm-level and national-level factors. Theoretical contribution/Originality: This study provides a new insight about the role of R&D expense with respect to the export intensity of the enterprise in transition economies. Practitioner/Policy Implications: This study suggests firms to continuously engage in innovation to gain a sustainable competitive advantage when exporting to other countries. Research limitation/ Implication: Further research may consider a bigger sample size and utilise time-series or panel data. Keywords: Export Intensity, R&D Intensity, Transition Economy, Viet Nam JEL Classification: F23, M16